Evaluation of Donor Site Pain After Fractional Autologous Full-Thickness Skin Grafting - Jaller, Jose A. (Adv Wound Care (New Rochelle), 2018)
Background: Despite the development of numerous wound treatment alternatives, 25% to 50% of leg ulcers and >30% of foot ulcers are not fully healed after 6 months of treatment. Autologous skin grafting is a time-tested therapy for these wounds; however, the creation of a new wound in the donor area yields a considerable limitation to this procedure. Innovation: Fractional autologous full-thickness skin grafting (FFTSG) is a technique wherein multiple small full-thickness skin grafts (FTSGs) are harvested with possibly minor donor-site comorbidities. The first device used to harvest FFTSG (ART™ system, Medline, Northfield, IL) is a device capable of harvesting >300 small FTSGs and transferring them to a target wound. Objective: To better evaluate patients' clinical experience, we sought to evaluate pain at the donor site associated with this procedure. Approach: Pain was assessed with numeric visual analog pain scales at days 1, 2, 4, and 7. Nine subjects underwent this procedure with only six of them reporting any level of pain on day 1, and none disclosing pain after day 2. Conclusion: In this study, we evidenced that this device manages to harvest FTSGs with minimal associated pain. Future research will need to evaluate other aspects of the procedure as well as long-term outcomes at the donor and recipient areas.